PERANCANGAN SISTEM TAGIHAN PENGGUNAAN AIR BULANAN PADA HUNIAN KOS BERBASIS WEB - Devri Bayu Perdana Putra; sujono sujono (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
The management of water billing in boarding houses often faces problems related to accuracy and fairness due to manual recording systems. This study aims to design a web-based monthly water billing system that can calculate and present water usage charges accurately for each room. The system was developed using the Waterfall method, which includes requirement analysis, system design, implementation, and testing stages. Water consumption data are processed to generate monthly bills based on predefined tariffs and stored in a database for reporting purposes. The application was implemented using PHP and MySQL. System testing using black-box testing shows that the billing calculation and reporting functions run correctly. The proposed system is expected to improve accuracy and efficiency in water billing management for boarding houses. The testing results indicate that the system is able to accurately calculate water bills based on usage data and predefined tariffs, as well as automatically generate monthly reports.